Health education, social media, and tensions of authenticity in the 'influencer pedagogy' of health influencer Ashy Bines. Issue 4 (2nd October 2022) - Hendry, Natalie Ann; Hartung, Catherine; Welch, Rosie
ABSTRACT: Health and wellness influencers are often criticised as dubious and unqualified sources of health education, presenting highly curated, commercialised lifestyles via social media platforms such as Instagram. While these critiques are important, they also present a narrow reading of complex digital cultures. In this paper, we examine a digital ethnographic case study of Australian entrepreneur and health influencer, Ashy Bines. We argue that Bines' pedagogical expertise is made possible through her seemingly contradictory media practices and messages, whereby she cultivates an 'authentic' personal experience for her followers. We frame these productive tensions in her social media practices as a form of 'influencer pedagogy' – the indirect, mediated processes of education produced through relatable interactions between influencers and their followers on social media platforms. We do not assess whether influencer pedagogy is 'good' or 'appropriate' but instead explore how influencers like Bines cultivate authenticity and expertise, and thus pedagogical potential.